Hankel Operators on the Weighted LP-Bergman Spaces with Exponential Type Weights. (12th February 2014) - Cho, Hong Rae; Seo, Jeong Wan
Abstract : We characterize the boundedness and compactness of the Hankel operator with conjugate analytic symbols on the weighted L P -Bergman spaces with exponential type weights.